Prevalence of resistance to sdhi fungicides in populations of the black and yellow sigatoka pathogens from bananas in southeastern Brazil - Silva, Tatiane Carla [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
The objective of the first chapter of this study was to develop and validate a digital fungicide sensitivity assay based on resazurin, called COL-assay, for plant fungal pathogens of the Mycosphaerella and Pyricularia genera. The proposed assay was based on colorimetric estimates of resazurin reduction, which was used as a metabolic indicator of fungal respiration activity in microplate cultures. Yellow and black Sigatoka pathogens and the wheat blast pathogen were used as fungal models. The classic spectrophotometric detection assay (SPEC- assay) was compared with the proposed COL-assay, based on digital image analysis of microplate cultures captured with cell phone cameras in a homemade transilluminator. It was observed that the COL-assay had similar precision to the SPEC-assay, resulting in similar fungicide sensitivity categories for resistant or sensitive fungal isolates and high precision. Since the complete methodology of the COL-assay and the homemade transilluminator were shared, the assay is likely to be adopted as an affordable means of monitoring fungicide resistance of important plant fungal pathogen populations such as M. fijiensis, M. musicola, and P. oryzae Triticum and Oryzae lineages. Based on the classic spectrophotometric detection assay (SPEC-assay) plus resazurin use, in the second chapter of this study, we detected that resistance to SDHI fungicides is widespread in populations of black and yellow Sigatoka pathogens in banana plantations in southeastern Brazil. The black and yellow Sigatoka disease complex (CDS), caused by Mycosphaerella fijiensis (Mf) or Mycosphaerella musicola (Mm), respectively, is one of the most destructive fungal leaf spot diseases affecting commercial banana fields worldwide, leading to significant yield losses. In Brazil, SDHI fungicides labeled for BSDC management since 2014 present a high risk of resistance emergence if deployed intensively and in isolation or in mixtures with other high-risk fungicides, as recommended for over eight years. To fill a current information gap on the occurrence and prevalence of resistance to SDHI fungicides, this study determined the levels of sensitivity to boscalid and fluxapyroxad in four CDS pathogen populations sampled in 2020 from three distinct geographical regions with contrasting fungicide management systems. Out of a total of 67 isolates, the prevalence of detected resistance to SDHI fungicides was 94.0% for boscalid and 59.7% for fluxapyroxad. Only 1.5% of isolates were sensitive to both fungicides. We also determined the association between sensitivity levels and changes in corresponding fungicide target genes (SdhB, C, and D). The boscalid and fluxapyroxad EC 50 values were highest in the Mf SPVR-CI population with intensive fungicide management, followed by Mm SPNW-C and Mm MGN-C. The Mm SPNW-O population from an organic banana field had the lowest average EC50s. Among the 10 Mf and 57 Mm isolates sequenced only, one (SdhC N55D) and two (SdhB E196Q and SdhD N66K) Sdh target site alterations, respectively, were detected. An efflux pump mechanism was also detected in Mf conferring resistance to fluxapyroxad. As resistance to SDHI fungicides is already prevalent, indicating simultaneous emergence in all three geographical regions, these results highlight the importance of limiting the deployment of SDHI fungicides for CDS management as a fundamental resistance management strategy.

O objetivo do primeiro capítulo deste estudo foi desenvolver e validar um ensaio digital de sensibilidade a fungicidas baseado na resazurina, denominado COL-assay, para patógenos fúngicos vegetais dos gêneros Mycosphaerella e Pyricularia. O ensaio proposto foi baseado em estimativas colorimétricas de redução de resazurina, que foi usada como um indicador metabólico da atividade de respiração fúngica em culturas de microplacas. Os patógenos de Sigatoka amarela e negra e o patógeno de brusone do trigo foram utilizados como modelos fúngicos. Foi comparado o ensaio de detecção espectrofotométrica clássico (SPEC-assay) com o COL-assay proposto, com base na análise de imagens digitais das culturas em microplacas capturadas com câmeras de celular em um transiluminador caseiro. Foi observado que o COL-assay teve precisão semelhante ao SPEC-assay, ou seja, resultou em categorias de sensibilidade a fungicidas semelhantes para isolados fúngicos resistentes ou sensíveis e alta precisão. Como a metodologia completa do COL-assay e a do transiluminador caseiro foram compartilhadas, o ensaio provavelmente será adotado como um meio acessível de monitorar a resistência a fungicidas de populações de importantes patógenos fúngicos vegetais como M. fijiensis, M. musicola e P. oryzae linhagens Triticum e Oryzae. Baseado no ensaio de detecção espectrofotométrica clássico (SPEC-assay) mais uso de resazurina, no segundo capítulo deste estudo, detectamos que a resistência aos fungicidas SDHI é generalizada em populações dos patógenos da Sigatoka negra e amarela em plantações de banana no sudeste do Brasil. O complexo de doenças da Sigatoka negra e amarela (CDS), causado por Mycosphaerella fijiensis (Mf) ou Mycosphaerella musicola (Mm), respectivamente, é uma das doenças de manchas foliares fúngicas mais destrutivas que afetam os campos comerciais de banana em todo o mundo, levando a perdas significativas de rendimento. No Brasil, os fungicidas de sítio específico SDHI rotulados para o manejo de BSDC desde 2014 apresentam um alto risco de surgimento de resistência se forem implantados intensivamente e isoladamente ou em misturas com outros fungicidas de alto risco, como recomendado por mais de oito anos. Para preencher uma lacuna de informações atual sobre a ocorrência e prevalência de resistência aos fungicidas SDHI, este estudo determinou os níveis de sensibilidade ao boscalida e fluxapiroxade em quatro populações dos patógenos CDS amostrados em 2020 de três regiões geográficas distintas com sistemas de manejo de fungicidas contrastantes. Num total de 67 isolados, a prevalência de resistência aos fungicidas SDHI detectada foi de 94,0% para boscalida e 59,7% para fluxapiroxade. Apenas 1,5% dos isolados foram sensíveis a ambos os fungicidas. Também determinamos a associação entre níveis de sensibilidade e mudanças nos genes-alvo de fungicidas correspondentes (SdhB, C e D). Os valores de EC50 do boscalida e do fluxapiroxade foram mais altos na população Mf SPVR-CI com manejo intensivo de fungicidas, seguida por Mm SPNW-C e Mm MGN-C. Entre os 10 isolados de Mf e 57 de Mm sequenciados, apenas uma (SdhC N55D) e duas (SdhB E196Q e SdhD N66K) alterações no local-alvo do Sdh foram detectadas, respectivamente. Um mecanismo de bomba de efluxo também foi detectado em Mf conferindo resistência ao fluxapiroxade. Como a resistência aos fungicidas SDHI já é prevalente, indicando emergência simultânea em todas as três regiões geográficas, esses resultados destacam a importância de limitar a implantação de fungicidas SDHI para o manejo de CDS como uma estratégia fundamental de manejo de resistência.
Prevalência de resistência aos fungicidas SDHI em populações dos patógenos da sigatoka negra e amarela em bananeiras no sudeste do Brasil.
Keywords: Fungal foliar pathogens; Fungicide resistance; High-risk fungicides; QoI; DMI; SDHI; Anti-microbial resistance phenotyping; Smart anti-resistance strategies; Surveillance- based spraying decision; Limiting fungicide sprays; Chemical control; SdhB; SdhC; SdhD; Fungicide resistance; Ec50; Resazurin